Students’ Perceptions of Effective TEFL Instructors in Cambodian Higher Education Institutions - Vanna Nourn (Journal of General Education and Humanities, 2023)
English language as a medium of instruction has been popular under globalization. English is now a popular medium of instruction and a major subject in Cambodia because most higher education institutions (HEIs) have adopted it as a common language for a learning curriculum. However, teaching English effectively has also been a concern in Cambodia because learners are not proficient or fluent in English. Moreover, most English classes have been taught by fresh graduates with little English teaching experience, and some instructors even teach subjects not in their field. Therefore, this study surveyed 265 year-4 TEFL students at three universities by asking them to rate their instructors’ teaching effectiveness. Instructors’ qualifications, content knowledge, pedagogical knowledge, pedagogical skills, and personal and interpersonal characteristics are used to examine students’ perceptions of effective TEFL instructors. The study showed higher percentages of students’ positive perceptions of the five domains of effective TEFL instructors. The findings are also consistent with the results of previous studies, suggesting that these qualities and characteristics should be must-have criteria for TEFL instructors in higher education. Thus, educational institutions should create certain criteria for selecting qualified university instructors. The findings can help the institutions develop human resources with these quality aspects or elements when selecting effective English language instructors. HEIs can use these criteria based on the results of this study, while TEFL instructors need to develop or improve themselves to have these qualities and other attributes for English teaching.